2004
DOI: 10.1534/genetics.103.026187
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Large Noncoding Sequence Is the Main Control Region of Maternally and Paternally Transmitted Mitochondrial Genomes of the Marine Mussel (Mytilus spp.)

Abstract: Both the maternal (F-type) and paternal (M-type) mitochondrial genomes of the Mytilus species complex M. edulis/galloprovincialis contain a noncoding sequence between the l-rRNA and the tRNA Tyr genes, here called the large unassigned region (LUR). The LUR, which is shorter in M genomes, is capable of forming secondary structures and contains motifs of significant sequence similarity with elements known to have specific functions in the sea urchin and the mammalian control region. Such features are not present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 77 publications
5
102
0
5
Order By: Relevance
“…In addition to the customary characteristics used to identify the mitochondrial control region of replication in animals (i.e., the largest noncoding region, increased AT content, and presence of repetitive elements and secondary structures) (Boore 1999;Saccone et al 2002;Cao et al 2004a;Saito et al 2005;Kuhn et al 2006;Oliveira et al 2007;Brugler and France 2008), we also used AT-skew values of protein-coding genes at fourfold redundant sites to locate the origins of heavy (O H ) and light (O L ) strand replication in freshwater bivalves. In most metazoans, the mitochondrial DNA genome replicates with a strand-asynchronous, asymmetric mechanism during which the parental heavy (H) strand becomes temporarily single-stranded DNA (ssDNA) while the nascent H strand is synthesized, and when the heavy strand synthesis reaches two-thirds of the genome, it exposes the O L and initiates the synthesis of a new light (L) strand in the opposite direction (Clayton 1982;Reyes et al 1998).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the customary characteristics used to identify the mitochondrial control region of replication in animals (i.e., the largest noncoding region, increased AT content, and presence of repetitive elements and secondary structures) (Boore 1999;Saccone et al 2002;Cao et al 2004a;Saito et al 2005;Kuhn et al 2006;Oliveira et al 2007;Brugler and France 2008), we also used AT-skew values of protein-coding genes at fourfold redundant sites to locate the origins of heavy (O H ) and light (O L ) strand replication in freshwater bivalves. In most metazoans, the mitochondrial DNA genome replicates with a strand-asynchronous, asymmetric mechanism during which the parental heavy (H) strand becomes temporarily single-stranded DNA (ssDNA) while the nascent H strand is synthesized, and when the heavy strand synthesis reaches two-thirds of the genome, it exposes the O L and initiates the synthesis of a new light (L) strand in the opposite direction (Clayton 1982;Reyes et al 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, these studies have shown (i) a high level of nucleotide sequence divergence but nearly identical gene content between F and M genomes within each species, (ii) an accelerated rate of molecular evolution of both the M and the F genomes compared to other animal mitochondrial genomes, (iii) an accelerated rate of molecular evolution of M genomes compared to F genomes, (iv) an absence of atp8 in mytiloid mussels, (v) the presence of a second trnM (i.e., transfer RNA gene for methionine) in mytiloid and veneroid bivalves, (vi) recombination between M and F genomes in mytiloid mussels, (vii) periodic ''role reversals'' (masculinization) of female-transmitted mtDNA in mytiloid mussels that are subsequently transmitted through sperm, (viii) different gene order between F and M genomes in unionoids, and (ix) the presence of a unique extension of the cytochrome c oxidase subunit II gene in the M (but not the F) genome in unionoids (reviewed in Breton et al 2007; see also Chapman et al 2008). An important hypothesis that has emerged from sequencing studies of species with DUI is that genderspecific sequences and/or sequences that exhibit the highest level of nucleotide divergence between the F and M genomes (i.e., regions that are under different, potentially gender-specific selective constraints and could, therefore, have different roles in either genome) are the most likely candidates for determining whether a mitochondrial genome will be transmitted maternally or paternally (Zouros 2000;Burzyń ski et al 2003;Cao et al 2004a;Breton et al 2006Breton et al , 2007Theologidis et al 2007;Venetis et al 2007;Cao et al 2009). For example, it has been demonstrated in marine mussels that masculinized type genomes (i.e., an F genome that ''masculinizes'' and takes on the role of the previous M genome) are essentially recombinants composed of an F genome's coding and control regions, with an additional standard M-type control region (Burzyń ski et al 2003;Breton et al 2006;Venetis et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We targeted a region spanning the end of lrn and the first variable domain of the CR in the F genome (VD1, Cao et al, 2004). Amplification was performed using the pair of universal primers AB15-AB16 (Filipowicz et al, 2008;Figure 2).…”
Section: The Studied Dna Regionmentioning
confidence: 99%
“…It is generally accepted that the most rapidly evolving part of the mitochondrial genome is the non-coding D-loop region believed to be the control region (CR) of mitochondrial replication and transcription. Therefore, to resolve the phylogeographic structure and demographic history of European Mytilus mussels at higher resolution, the CR seems to be a suitable marker (Cao et al, 2004;Song et al, 2013). Here we report the analysis of its polymorphism in mussels sampled in coastal waters around Europe from the White Sea to the Sea of Azov.…”
Section: Introductionmentioning
confidence: 99%